Namık Kemal'ın Hikayelerinde "İsim Hal Ekleri" (Journal of the College of Languages (JCL), 2017)
ÖzetBenim tezimin adlı "Namık kemal'ın Hikayelerinde isim hal ekleri"dir. Bu tezde ilk olarak Namık kemal'ın hayatı hakkında bilgi vermeye çalıştım. Sonra isim hal ekleri hakkında bilgi de verdim. Sonra Namık kemal'ın hikayelerinde geçen isim hal ekleri birer birer çıkarmaya çalıştım.XIX yüz yılında en önemli dönem Tanzimat dönemidir. Tanzimattan beri yeni hayat ihtiyaci ile yeni sanat anlayışı, birçok yeni kelime ve tamlamaların ortaya çıkıp, yerleşmesine sebep olmuştur. Namık kemal'ın mektuplarındaki birçok kelimeler, fikirler, kavramlar ve inanışlar, hepsi yeni değildir. Çoğu yaşıyan dilde kullanıyor, bir kısmı da sözlüklerde bulunuyordu. Fakat birer tamlama olarak yan yana gelince, o zamana kadar kullanılmıyan anlamda, çağdaş bir düşünce ile yeni bir nitelik kazanmış oluyordu.Abstract The present paper deals with (Suffixes of Name Cases in Namiq Kamal's Tales). It also presents information about Kamal's biography, trying to provide enough information about him. The paper provides information about suffixes of name cases, and then, it tackles these suffixes in Kamal's Tales. The Era of Organization is regarded as one of the most important ones during the 19th C. Ever since a new concept which meets the needs of modern art and literature was born. New words and terms appeared. These were behind the modernization and innovation of the literary and lingual development. The ideas, words, terms and beliefs that can be seen in Kamal's correspondence are not regarded as modern, the best part of them are used in daily conversations, others can be found in dictionaries. There are only few lexical items which were not in use by then. They relate to the modern new ideas. Suffixes of name cases are regarded very important part of the Trukish grammaras they are used in the daily conversations performed by the public. This is why they have an extreme importance in Turkish grammar and were taken into consideratiuon by the writers whether in linguistics or in literature. Key Words: The regulations, Namik Kemal, Tales Namik Kemal, Sultan Aziz in London and Suffixes cases Name